Swiss Monetary Policy 2000-2009 - Hans Genberg; Stefan Gerlach (Swiss Journal of Economics and Statistics, 2010)
In January 2000 the Swiss National Bank adopted a new monetary policy framework incorporating a price stability objective defined as (any rate of) CPI inflation below 2 percent. We contrast this framework with inflation targeting strategies and review the SNB's policy decisions since its introduction. Empirical results indicate that in setting policy the SNB reacts in much the same way as inflation targeting central banks. The recent sharp reduction in the policy rate is consistent with the estimated reaction function until the second quarter of 2009 when the zero bound became binding, while the deterioration of economic conditions still called for further monetary easing. This may explain the unconventional monetary policy measures adopted since then.
Keywords: E43; E52; E58; 330; Inflation targeting; SNB; empirical reaction functions; Taylor rule